Increasing Holistic Intelligence with Digital Literacy in Islamic Boarding Schools: Case Study at Universitas Darussalam Gontor - Rochmat, Cecep Sobar (UIN Sunan Gunung Djati Bandung, 2024)
This research aims to review the implementation of digital literacy culture in forming holistic intelligence at University of Darussalam Gontor students. In the era of digital transformation, it has affected all aspects of life, including the world of education. Through digital literacy, education can predict developments in information and digital technology by presenting updates of relevant knowledge and understanding that can be accessed easily and quickly. The research method used in this research is descriptive qualitative with a case study approach. The research subjects were students at University of Darussalam Gontor. Obtaining research stamps is taken from student interviews that match the research topic criteria. Because digital literacy affects students' intelligence holistically both spiritually, physically, intellectually and emotionally. The results of this research are that University of Darussalam Gontor students are able to increase holistic intelligence by wisely using digital literacy media. Thus forming 4 factors that are relevant in the digital transformation era, namely, 1) creativity in innovative thinking, 2) gaining spiritual and religious understanding, 3) being able to interact with society and the environment, 4) being wise in using social media. Therefore, students are expected to be able to increase their holistic intelligence to be able to process data, interact, collaborate and be creative. Therefore, the role of students in digital literacy has a significant influence in forming and improving holistic intelligence